Ramón Martínez Escamilla. La fuerza de trabajo en el capitalismo mexicano. México : HADISE, 1974. 200 p. - Hernández Millán, Abelardo (Estudios Demográficos y Urbanos, 1976)
RAMÓN MARTÍNEZ ESCAMILLA, La fuerza de trabajo en el capitalismo mexicano, México, HADISE, 1974.